Organizational climate on employees’ work passion: a review - P. Yukthamarani Permarupan; Abdullah Al- Mamun; Roselina Ahmad Saufi; Noor Raihani Zainol (2013)
This paper presented in-depth review of recent literature focused on organizational climate and employee’s work passion and organizational commitment within academician of public and private Universities in Malaysia. An argument is put forward that there is a causal link between good organizational climate and the employees work passion and commitment in an organization. A conceptual model of organizational climate and employee’s work passion and organizational commitment is presented that provides an explanation of the linkage between these variables. This paper addressed the employee’s needs and expectation from the employer in the aspect of organizational climate and commitment. Thus, by exploring the recent literature, this paper provides a critical review about the role of organizational climate, and therefore, enhances further knowledge and understanding of employee’s work passion as well as organizational commitment.